High neutrophil percentage and neutrophil-lymphocyte ratio in acute phase of ischemic stroke predict cognitive impairment: A single-center retrospective study in China - Shang, Tianling; Ma, Bo; Shen, Yanxin; Wei, Chunxiao; Wang, Zicheng; Zhai, Weijie; Li, Mingxi; Wang, Yongchun; Sun, Li (Frontiers in Neurology, 2022)
Background and Aims: Recently, various hemocyte and blood cell ratios have garnered researchers’ attention, as a low-cost, widely prevalent, and easy to measure index for diagnosing and predicting disease. Therefore, we sought to investigate the effect and predictive value of the peripheral blood neutrophil percentage and neutrophil/lymphocyte ratio (NLR) in the acute phase of ischemic stroke (AIS) in post-stroke cognitive impairment (PSCI). Methods: We selected 454 patients with mild AIS and acquired general clinical data. The patients were divided into PSCI and post-stroke no cognitive impairment (PSNCI) groups according to their Montreal Cognitive Assessment (MOCA) scores. We assessed whether there were differences in clinical data, peripheral blood neutrophil percentage, and NLR values between the different groups. We also analyzed the independent influences on the occurrence of PSCI using a binary logistic regression. Receiver operating characteristic (ROC) curves were used to analyze the predictive value of the above inflammatory indicators and models containing different inflammatory indicators for PSCI. Results: Altogether, 454 patients were included, of whom 253 (55.7%) were in the PSCI group, with a mean age of 62.15 ± 7.34 years and median neutrophil percentage and NLR of 0.64 (0.32-0.95) and 2.39 (0.71-54.46), respectively. Both neutrophil percentage (adjusted OR, 1.025; 95% confidence interval, 1.005-1.406) and NLR as a categorical variable (Q5, adjusted OR, 2.167; 95% CI, 1.127-4.166) were independent risk factors for PSCI, and the Q5 group (NLR ≥ 4.05) had significantly worse overall cognition and executive function. Conclusions: Neutrophil percentage and NLR in the acute phase of AIS were independently associated with PSCI, and a high NLR was strongly associated with executive function. In addition, neutrophil percentage and NLR have diagnostic value for PSCI.